Exogenous Ethylene Promotes Peel Color Transformation by Regulating the Degradation of Chlorophyll and Synthesis of Anthocyanin in Postharvest Mango Fruit - Chen, Mingmin; Gu, Hui; Wang, Lirong; Shao, Yuanzhi; Li, Rui; Li, Wen (Frontiers in Nutrition, 2022)
Due to geographical location and climatic factors, post-harvest storage and preservation of tropical fruits and vegetables are still facing huge challenges. Ethephon (ETH) is widely used as an ethylene donor to achieve commercial color and flavor of climacteric fruits. However, the effect of ETH on fruit coloration was affected by many factors, such as fruit species, plant hormones and storage conditions. In this study, the main mango variety‘Guifei’in Hainan, China, was used to study the effects of different concentrations of ETH on fruit ripening and coloration during storage at 25℃. Results showed that post-harvest treatment with ETH (300, 500, 900 mg·L-1) enhanced the activities of ACS and ACO, stimulated the release of endogenous ethylene, and accelerated fruit softening and color transformation. Compared with control, ETH treatment not only accelerated the breakdown of chlorophyll with higher activities of Chlase and MDCase, but also induced the synthesis of carotenoid and anthocyanin with higher activities of PAL, CHI, DFR and UFGT. Moreover, the changes in DFR and UFGT activities coincided with the increase of ETH concentration. Further correlation analysis showed that the production of endogenous ethylene induced by ETH was significantly negatively correlated with firmness and chlorophyll content, whereas positively correlated with MDA content and anthocyanin content. This study suggests that the positive effect of ETH on ‘Guifei’ mango color transformation is concentration-dependent within a certain concentration range. Anthocyanin is the main pigment for red formation of ‘Guifei’ mango and DFR and UFGT may play critical roles in anthocyanin synthesis. ETH promoted the red coloration by promoting the release of endogenous ethylene and enhancing the activities of anthocyanin synthesis enzymes.